Proses Pemecahan Masalah Matematika Ditinjau dari Gaya Belajar Siswa - Anggelia Willia; Pradipta Annurwanda; Rizki Nurhana Friantini (AlphaMath : Journal of Mathematics Education, 2020)
The purpose of this study was to find out the description of the problem solving process in each type of learning style for grade X of MIPA B students in SMA Negeri 1 Ngabang in Academic Year 2019/2020, Landak Regency. This research is a qualitative research. The subjects in this study were 6 (six) students of grade X MIPA B of SMA Negeri 1 Ngabang. The selection of research subjects is based on a purposive sampling technique. Data analysis techniques used in this study are data reduction, data display, and conclusion drawing / verification. The results of this study indicate that 1) students with visual learning styles are able to understand problems well, are able to make easy and simple settlement plans so that they can do calculations correctly, and can re-examine the results of answers by re-reading the questions and the results of the answers, 2) students with the auditory learning style able to understand the problem well, able to make an easy solution to the plan, can do the calculations correctly, and can re-examine the results of the answers by re-reading the questions and the results of the answers, 3) students with kinesthetic learning styles are able to understand the problem but have not been able to make plans and carry out plans so that it is difficult to do the calculations correctly and at the stage of re-checking the results kinesthetic students can reexamine the results of the answers by rereading the questions and the results of the answers.